A Novel Non-integer Indirect Adaptive Control for Non-integer Order Systems with Non-prior Knowledge - Bourouba, B.; Ladaci, S. (Engineering, Technology & Applied Science Research, 2020)
In this study, a new non-integer indirect adaptive control method with reference model is suggested for the class of non-integer order systems. The objective of model reference control is to include the output of the given reference fractional model in tracking the output of a controlled plant by using the concept of on-line goal adaptation. The stability of the closed-loop system is analyzed via the Lyapunov method. Finally, Matlab simulation results are presented to illustrate the effectiveness of the proposed method of indirect fractional model reference adaptive control.